The rye baker : classic breads from Europe and America - Ginsberg, Stanley (W.W. Norton & Company, 2016)
"True rye bread -- the kind that stands at the center of northern and eastern European food culture -- is something very special. With over 70 classic recipes, The Rye Baker introduces bakers to the rich world of rye bread from both the old world and the new. Award-winning author Stanley Ginsberg presents recipes spanning from the immigrant breads of America to rustic French pains de seigle, the earthy ryes of Alpine Austria and upper Italy, the crackly knäckebröds of Scandinavia, and the diverse breads of Germany, the Baltic countries, Poland, and Russia. Readers will discover dark, sour classic Russian Borodinsky; orange and molasses-infused Swedish Gotländ Rye; nearly black Westphalian Pumpernickel, which gets its musky sweetness from a 24-hour bake; traditional Old Milwaukee Rye; and bright, caraway-infused Austrian Country Boule. Rounding out this treasury are reader-friendly chapters on rye's history, unique chemistry, and centuries-old baking methods. Advanced bakers will relish Stanley's methods, ingredients, and carefully sourced recipes, while beginning bakers will delight in his clear descriptions of baking fundamentals. The Rye Baker is the definitive resource for home bakers and professionals alike,"--Amazon.com.